ANALISIS RASIO KEUANGAN SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA PERUSAHAAN ROKOK YANG GO PUBLIK DI BURSA EFEK INDONESIA TAHUN 2016 - 2020 - Moch Irsad; Sri Sudarsi; Cahyani Nuswandari (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the company's financial performance in terms of liquidity, solvency, activity, and profitability ratios and to examine the effect of liquidity ratios, solvency ratios, and activity ratios on the company's profitability ratios. This research was conducted on cigarette companies that went public on the Indonesia Stock Exchange in 2016-2020. The number of cigarette companies that went public on the IDX was 4 (four) companies. The sampling technique used was purposive sampling, the number of samples during the study period was 20 samples and 16 samples metJthe criteria. Data analysis was carried out by 1) comparative analysis ofJfinancial ratios, and 2) multiple linear regression analysis assisted by the application of the SPSS program. The results of research on the financial performance of cigarette companies that went public on the IDX in 2018-2020 both in the short and long term the company has the ability to pay obligations (debt) and the company can use assets effectively and is able to achieve high profitability. The results of the study can prove that the liquidity ratio, solvency ratio, and activity ratio have a significant effect on the profitability ratio.